The Russian-language Literature — A Clash of Cultures (Филологический класс, 2015)
The author introduces the differentiation of the Russian literature as the national one and of Russian-language literature as the multi-ethnic one though written in Russian. The «Russian-language» prose of the Soviet times characterizes with extraordinary ways constructing a syncretic model of the world: a) placing odd-ethnic genres, b) unusual exchange of fictional national archetypes, c) dialogue relation between the national topos and the topos of the whole country, d) contamination of the Russian literary genre and the folk odd-ethnic one are worth special attention. It can be considered as a kind of heterogenic poetics.